2005
DOI: 10.1210/jc.2004-1933
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Testosterone (T) Alone or with Finasteride Increases Physical Performance, Grip Strength, and Lean Body Mass in Older Men with Low Serum T

Abstract: Testosterone (T) therapy in older men with low serum T levels increases lean body mass and decreases fat mass. These changes might improve physical performance and strength; however, it has not been established whether T therapy improves functional outcome in older men. Moreover, concerns exist about the impact of T therapy on the prostate in older men. The administration of finasteride (F), which partially blocks the conversion of T to the more potent androgen, dihydrotestosterone, attenuates the impact of T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
357
5
5

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 512 publications
(384 citation statements)
references
References 45 publications
(72 reference statements)
17
357
5
5
Order By: Relevance
“…Relative contraindications to be considered include elevated hematocrit, abnormal liver function studies, LUTS, and sleep apnea. A rare adverse event is the enlargement of prostate size, which can be prevented by the administration of finasteride [147,148]. It has also been suggested that large numbers of men with low to lownormal testosterone levels would benefit from testosterone screening when they are evaluated for ED and that testosterone therapy may improve the response of PDE5 inhibitors [70,71,73].…”
Section: Step Care 4: Hormonal and Nonhormonal Pharmacologic Treatmentmentioning
confidence: 99%
“…Relative contraindications to be considered include elevated hematocrit, abnormal liver function studies, LUTS, and sleep apnea. A rare adverse event is the enlargement of prostate size, which can be prevented by the administration of finasteride [147,148]. It has also been suggested that large numbers of men with low to lownormal testosterone levels would benefit from testosterone screening when they are evaluated for ED and that testosterone therapy may improve the response of PDE5 inhibitors [70,71,73].…”
Section: Step Care 4: Hormonal and Nonhormonal Pharmacologic Treatmentmentioning
confidence: 99%
“…Therapies associated to testosterone and other androgenic hormone treatment favor changes in body composition, especially in lean mass gain and neuromuscular adaptation (Allan et al 2008;Schroeder et al 2004;Page et al 2005;Kenny et al 2001;Schroeder et al 2003a). However, the effects of these types of treatment are not fully understood, since their objectives, dosages and duration as well as the association with physical activity adds complexity to the data provided by the studies on this theme (Kenny et al 2000;Morley et al 2003;Snyder et al 1999;Tenover 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Testosterone replacement may be effective in reversing age-dependent body composition changes and associated morbidity [71]. Testosterone administration improves body composition: a decrease of fat mass, increase of LBM [37,72,73]. In most of these studies, the body weight change did not differ significantly.…”
Section: Muscle Mass and Strengthmentioning
confidence: 95%
“…In the past decade evidence has been produced of the benefit of androgen treatment on multiple target organs of hypogonadal men, and recent studies show short-term beneficial effects of testosterone in older men that are similar to those in younger men [34][35][36][37].…”
Section: Benefits Of Testosterone Of Replacement Therapymentioning
confidence: 99%
See 1 more Smart Citation